Diversidad y reconocimiento de la producción académica en los sistemas de evaluación de la investigación en Colombia (2014)
ABSTRACT: This article reviews both those products resulting from research processes in the 6 best ranked universities in Colombia according to international rankings, and documents from the National System of Science, Technology and Innovation. Exploratory network analyses and descriptive statistics are used to analyse the institutions’ documents with respect to their research production goals and performance evaluations. The international discussion about what should and what should not be measured in order to determine the impact of scholarly and scientific research is shown not to take into account many forms of new knowledge production, resulting in such products remaining invisible.